Two new species of Nemouridae (Plecoptera) from Vietnam - Fochetti, Romolo; Ceci, Massimo (Zootaxa, 2017)
Two new species belonging to the family Nemouridae, Nemoura kontumensis sp. nov. and Amphinemura konplongensis sp. nov. are described from the Central Highlands of Vietnam. Remarks on the affinities with related species are given.